The thermodynamic analytical models for steady-state of linear friction welding based on the maximum entropy production principle. (5th September 2017) - Xiong, J.T.; Zhou, W.; Li, J.L.; Zhang, F.S.; Huang, W.D.
Abstract: A simple model developed on clear physical bases always is one of the major challenges for the study of linear friction welding. Based on the thermodynamic framework extracted from the Onsager-Ziegler maximum entropy production principle (OZ-MEPP), a 2D analytical thermodynamic model is established to characterize the steady-state of the severe plastic deformation (SS-SPD) systems produced by LFW. The model has the features of self-consistency and directive prediction, which can successfully predict all of the response parameters for the SS-SPD system merely from the initial conditions (the welding parameters, sizes and thermo-physical parameters of the specimens). The model is examined by the corresponding experimental results of seven alloys, which indicates that the accuracy and generality of the model is satisfactory. Moreover, the model also provides a thermodynamic and quantitative explanation for the temperature distribution in the SS-SPD system, friction coefficient of stick friction and the direction of adiabatic shear. Graphical abstract: Highlights: A 2D simple thermodynamic analytical model was developed for characterizing the steady-state of linear friction welding without assuming or measuring values of any response parameters. A cosine distribution was deduced for the temperature field of the severe plastic deformation region of the joint. The friction coefficient of the steady-state of linear friction welding was calculated and verified by experiments.